Theology before Church Polity: A Fourteenth-Century Guide for Mendicant Preachers on the Good Shepherd. - Nodes, Daniel (Medieval Sermon Studies, 2020)
The recurrent shepherding motif in the Bible gained even greater prominence from Jesus's reference to himself as the Good Shepherd in John 10 and in related texts like the Lost Sheep of Luke 15 and the mission to feed the flock of God in Matthew 15 and i Peter 2. It was further promoted by the inclusion of those texts in lectionaries, and so shepherding became a regular topic of sermons. The analogy facilitated the connection between Christ as Shepherd and leaders caring for subordinates. The main practical lesson was on leadership, protection, and devotion, but the image also elicited lessons on the divine nature itself: its permanence, for example, and its providence and omniscience. The collation of Frater Petrus on the Good Shepherd offers a new witness to an interpretive tradition found in exegetes including Augustine, Bonaventure, and Nicholas of Cusa, but it is exclusively theological. This emphasis epitomizes the theological inclination of his other collations for a full year of Sundays and major feasts. The combined thematic and codicological evidence suggests that the collations of Frater Petrus were meant to reinforce a theological foundation for young mendicants before they moved on to preaching in the world.